PARENTING CHILDREN BY MOTHER WHO VICTIM DOMESTIC VIOLENCE: A LITERATURE REVIEW - Indah Rizky Valiant; Elsye Maria Rossa (Faculty of Public Health, Andalas University, 2021)
Global prevalence women who experience domestic violence is 30% of all women who are married.Domestic violence affects both mother and child, as well as parenting by mother. The purpose of this literature review is to explore and identify parenting children by mother who victim domestic violenc. This literature review uses 4 databases namely Ebsco, Pubmed, Scopus and ScienceDirect. The selection of studies in this literature review used inclusion and exclusion criteria. Inclusion criteria used in the selection of literature review studies are full text, journals or article in English, journal about parenting children by mother who victim domestic violence, and jornals of the last 2 years (2017-2019. Based on 12 journals analyzed there are 3 major themes, namely relationship mother-child factors, parenting strategies in domestic violence and parenting behavior. Parenting behavior is inseparable form the mother’s strategy and the relationship mother-child. The need to have a good relationship and use the right strategies to form positive parenting behavior.